BATAGAK URANG TUO NAGARI DI BALAI BARU KECAMATAN KURANJI KOTA PADANG - Redo Ilhamsyafitra (Jurnal Elektronik WACANA ETNIK, 2017)
This article describes the implementation of the Batagak Urang Tuo Nagari ceremony. Batagak Urang Tuo Nagari is one of the most important ceremonies in the traditional order in the Balai Baru because traditional communities are beginning to be aware of the importance of the role of Urang Tuo Nagari in society and in other areas of Minangkabau.In Batagak Urang Tuo Nagari the ninik mamak, bundo kanduang, cadiak pandai, and anak kemenakan still retain the important elements contained in the procedures for their implementation. Keywords: Traditional Ceremony, Batagak Urang Tuo Nagari, Balai Baru